Changes in soil phosphorus fractions in response to long-term phosphate fertilization under sole cropping and intercropping of maize and faba bean on a calcareous soil - Liao, Dan; Zhang, Chaochun; Lambers, Hans; Zhang, Fusuo (Plant and soil, 2021)
Background and aims Understanding how soil phosphorus (P) fractions change is critical to achieve more efficient soil P use in a highly P-sorbing calcareous soil. Methods The fields were managed without or with annual P fertilizer (40 kg P ha − 1 ), continuously growing sole cropping or intercropping of maize and faba bean. Soil samples (0–200 mm) were collected at the start of the experiment and eight years later, and we evaluated P fractions using sequential fractionation. Results Maize/faba bean intercropping had an average land equivalent ratio (LER) of 1.2, a similar P content as sole maize, while both acquired more P than sole faba bean. Compared with the original soil P fractions in 2009, three cropping systems, regardless of P fertilization, depleted the labile P pool (Resin-P and NaHCO 3 -P i ), while Residual-P and NaHCO 3 -P o accumulated. Eight years of no P input showed sole maize mainly depleted NaOH-P i and conc. HCl-P i , sole faba bean depleting NaOH-P o , while intercropping depleted the most abundant P fraction, 1 M HCl-P i , in addition to NaOH-P i . However, long-term P application caused the cropping systems to accumulate 1 M HCl-P i while depleting the conc. HCl-P o fraction; both sole faba bean and intercropping showed accumulation of NaOH-P i , while depleting NaOH-P o . Conclusions Long-term appropriate P input enhanced the mineralization of mod-labile and non-labile organic P and accumulation of mod-labile inorganic P. Sole maize consistently depleted inorganic P and sole faba bean without P input depleted organic P, while intercropping accessed P pools varying with P input.